Relationship Between Strength Parameters and Functional Performance Tests in Patients With Severe Knee Osteoarthritis. Issue 8 (7th March 2019) - Bily, Walter; Sarabon, Nejc; Löfler, Stefan; Franz, Carlo; Wakolbinger, Robert; Kern, Helmut
Abstract : Background: Decreased leg muscle strength is a major determinant of reduced function in patients with knee osteoarthritis (OA). The identification of a strength parameter that is best correlated with functional performance is important for monitoring rehabilitation results. Objective: To determine which muscle strength measurements show the highest correlation with functional capacity in patients with severe knee OA shortly before total knee arthroplasty (TKA). Design: Cross‐sectional exploratory study. Setting: Outpatient rehabilitation department at a university teaching hospital. Patients: The sample included 75 patients (51 female) scheduled for primary TKA, recruited through multistage sampling. Methods or Interventions: Independent variables were peak isometric, isokinetic concentric, and eccentric leg extensor strength measured on the leg press, as well as peak isometric knee extensor strength measured on the strength chair. Two multiple regression analyses were performed, one including all strength measures and the other including all of the strength ratios. Pearson correlation coefficients were calculated between the strength measures and functional test scores. Main Outcome Measurements: Dependent variables were the Timed Up and Go Test (TUG) and the Stair Test (ST). Results: The regression analysis including all strength measures could explain 11.9% of the variance of the TUG ( P  = .068, not significant [NS]) and 21.5% of the variance of the ST ( P  = .009, significant). The regression model for the strength ratios explained 11.8% of the variance of the TUG ( P  = .090, NS) and 6.3% of the ST ( P  = .217, NS). Conclusions: Although univariate analysis confirmed significant correlations between strength measurements and functional tests, multiple regression analysis revealed a higher predictive value for the ST than for the TUG. The use of both muscle strength tests and performance‐based function tests is advisable to evaluate functional impairments of patients with knee OA. Level of Evidence: III